Masyarakat Ekonomi ASEAN 2015: Antara Musibah Dan Berkah Bagi UMKM Indonesia - Sulistyo Seti Utami (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2014)
In the near future ASEAN Economic Community (AEC) will soon be carried out in ASEAN countries; it has become an interesting issue for various parties, such as government, private businessmen, entrepreneurs, professionals, economists, academicians, etc. However, until at present we still don’t clearly know which sectors of Indonesia will become the one which is a primary. Even with the variety and number of Micro, Small, and medium Enterprises (UMKMs) which are now available almost up to 98,9%, they will become problems for Indonesia in facing the AEC market. Due to of most the UMKMs still don’t have strong competitiveness to enter the common market of ASEAN. In addition, they, UMKMs, still haven’t realized and even haven’t still understood yet what ASEAN common market is, even though it will be applied soon in our country in 2015. Factually, there are a lot of UMKMs in Indonesia that must be seriously paid attention and protected by our government. Our country must be able to make UMKM sectors to become a strong economic base for Indonesia. Referring to the idea above, this writing will try to describe what problems will be faced by UMKMs in entering ASEAN Common Market or AEC market and will also try to explain how UMKMs could become excellent sectors especially on their products which have local advantages which are owned by Indonesia.